Two cases of infections due to multidrug-resistant Bacteroides fragilis group strains. - Katsandri, Anastasia; Papaparaskevas, Joseph; Pantazatou, Angeliki; Petrikkos, Georgios L; Thomopoulos, Georgios; Houhoula, Dimitra P; Avlamis, Athina (J Clin Microbiol, 2006)
Bacteroides fragilis group strains are still considered susceptible to most antimicrobial agents used for the treatment of infections caused by anaerobic organisms. We describe two cases of infections due to isolates simultaneously resistant to clindamycin, tetracycline, cefoxitin, piperacillin-tazobactam, and imipenem and, in one of the two cases, to metronidazole. Such infections, although still rare, do exist and tend to complicate treatment.
Keywords: Aged; Anti-Bacterial Agents; Bacteroides fragilis; Bacteroides Infections; Drug Resistance, Multiple, Bacterial; Humans; Male; Microbial Sensitivity Tests